Demand drivers for charging infrastructure-charging behavior of plug-in electric vehicle commuters. (November 2019) - Chakraborty, Debapriya; Bunch, David S.; Lee, Jae Hyun; Tal, Gil
Highlights: Home electricity cost strongly influences the choice of charging location by PEV commuters. Free workplace charging may shift home charging events to the workplace; can cause congestion. Access to Level 2 chargers at home incentivizes home charging. Apartment dwellers are more dependent on non-home compared to PEV commuters in detached homes. Longer electric range will change charging needs and demand for infrastructure in the future. Abstract: The public as well as the private sector that includes automakers and charging network companies are increasingly investing in building charging infrastructure to encourage the adoption and use of plug-in electric vehicles (PEVs) as well as to ensure that current facilities are not congested. However, building infrastructure is costly and, like road congestion, when there is significant uptake of PEVs we may not be able to "build out of congestion." Modelling the choice of charging infrastructure of more than 3000 PEV drivers who had the opportunity to select among home, work, and public locations, we focus on understanding the importance of factors driving demand such as: the cost of charging, driver characteristics, access to charging infrastructure, and vehicle characteristics. We find that differences in the cost of charging play an important role in the demand for charging location. PEV drivers tend to substitute toward workplace charging when they pay a higher electricity rate at home, more so when the former is free. Additionally, socio-demographic factors like dwelling type and gender, as well as vehicle technology like electric range, influence the choice of charging location.